Unique structural and mechanistic properties of mycobacterial F-ATP synthases : implications for drug design - Kamariah, Neelagandan (2020)
The causative agent of Tuberculosis (TB) Mycobacterium tuberculosis (Mtb) encounters unfavourable environmental conditions in the lungs, including nutrient limitation, low oxygen tensions and/or low/high pH values. These harsh conditions in the host triggers Mtb to enter a dormant state in which the pathogen does not replicate and uses host-derived fatty acids instead of carbohydrates as an energy source. Independent to the energy source, the bacterium’s energy currency ATP is generated by oxidative phosphorylation, in which the F1FO-ATP synthase uses the proton motive force generated by the electron transport chain. This catalyst is essential in Mtb and inhibition by the diarylquinoline class of drugs like Bedaquilline, TBAJ-587, TBAJ-876 or squaramides demonstrated that this engine is an attractive target in TB drug discovery. A special feature of the mycobacterial F-ATP synthase is its inability to establish a significant proton gradient during ATP hydrolysis, and its latent ATPase activity, to prevent energy waste and to control the membrane potential. Recently, unique epitopes of mycobacterial F1FO-ATP synthase subunits absent in their prokaryotic or mitochondrial counterparts have been identified to contribute to the regulation of the low ATPase activity. Most recent structural insights into individual subunits, the F1 domain or the entire mycobacterial enzyme added to the understanding of mechanisms, regulation and differences of the mycobacterial F1FO-ATP synthase compared to other bacterial and eukaryotic engines. These novel insights provide the basis for the design of new compounds targeting this engine and even novel regimens for multidrug resistant TB.